2018
DOI: 10.1007/s11661-018-4483-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Microstructure and Alloy Chemistry on Hydrogen Embrittlement of Precipitation-Hardened Ni-Based Alloys

Abstract: The sensitivity to hydrogen embrittlement (HE) has been studied in respect to precipitation size distributions in two nickel base superalloys, Alloy 718 (UNS N07718) and Alloy 945X (UNS N09946). Quantitative microstructure analysis was carried out by the combination of scanning and transmission electron microscopy and energy dispersive x-ray spectroscopy (EDS). While Alloy 718 is mainly strengthened by g¢¢, and therefore readily forms reduced sensitivity to HE compared to Alloy 718 when considering high streng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…If no grain boundary precipitates are present in the moderate aging condition, another cause, such as matrix precipitate coarsening, contributes to diminishing HE resistance with aging. In previous studies, γ' and γ" coarsening during aging has been shown to influence HE susceptibility in Ni-base alloys [2,4,10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If no grain boundary precipitates are present in the moderate aging condition, another cause, such as matrix precipitate coarsening, contributes to diminishing HE resistance with aging. In previous studies, γ' and γ" coarsening during aging has been shown to influence HE susceptibility in Ni-base alloys [2,4,10].…”
Section: Discussionmentioning
confidence: 99%
“…The objective of this initial survey was to identify conditions with comparable hardness but different degrees of δ formation in Alloy 718 and M23C6 formation in Alloy 945X. A similar hardness was sought to avoid strength-related effects causing differences in HE susceptibility between conditions [10,14]. The alloys were annealed at 1050 °C for 2.5 h to solutionize precipitates.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The manufacturing route of bolts involves the API heat treatment followed by cold rolling of threads, whereas, samples extracted from RB undergo electrical discharge machining followed by the heat treatment. The objective was to perform subsurface cracking analysis for the subsea bolts on the basis of microstructural results and to critically discuss the 718 subsea bolt vulnerability to HE in-service with the already established HAC theories for alloy 718 (which were subjected to different thermochemical treatments and product forms) [ [37]. The non-standard higher solution treatment at 1250˚C (because the melting Figure 1.…”
Section: Purposementioning
confidence: 99%
“…Some inclusions can initiate a pitting corrosion and could lead to environmentally assisted cracking, corrosion fatigue, hydrogen embrittlement. Therefore, the study of corrosion and mechanical properties of Ni-based alloys and their dependence on different inclusions became the object of attention in many studies [15,16,17,18,19,20].…”
Section: Introductionmentioning
confidence: 99%